The Market and Psychiatric Disorders - Ugolini, Beatrice (Social Science Learning Education Journal, 2017)
Particular economic interests and national and international financial demands condition the system according to which mental illnesses are assessed, diagnosed and treated. In the context of psychiatric pathologies, the market also exerts its influence through disease mongering, which consists in the tendency, operated by global pharmaceutical companies, to broaden the market, transforming common diseases into pathologies. Today, that which shifts the boundary between normal and pathological, in any case changing in accordance with the epochs and cultures, is the market strategy decided by âBig Pharmaâ. The construction of a psychiatric diagnostic category is, therefore, also the result of a commercial need, reinforced by a targeted sensitisation of public opinion. The creation of new pathologies is encouraged by a collective that requires, more than ever, the positioning and allaying of its own shadow.Â Key words: psychiatric disorder; Big Pharma; normal; pathological.